THE IMPACT OF II-C MERR (MIDDLE EAST RING ROAD) DEVELOPMENT ON BUILDING CHARACTERS THROUGH THE PLACE MAKING APPROACH - Susanti, Wiwik Dwi; Mutia, Fairuz; Utomo, Heru Prasetiyo (Border: Jurnal Arsitektur, 2019)
The construction of the MERR II-C highway is a series of projects in the Surabaya City Government connecting Gunung Anyarto Juanda. The impact of road construction is the splitting of the densely populated of kampong Gunung Anyar. The characteristics of the kampong penetrated by the road construction are formal and informal kampong. The sporadic character of the informal kampong is clearly visible from the debris of the remaining buildings, while the kampong formal is also visible from the neatly arranged character. At this time the character of the building trying to find identity because the character of informal kampong can still be detected but the influence of trade and service functions in MERR II-A and MERR II-B have begun to be seen. So that this research is considered important to determine the character of the building that appears the impact of the construction of the road MERR II-C. In mapping the character of the building using the place making approach, so it can know the building's character. The results showed that the character of the building formed was the character of commercial, service and residential buildings. Many new commercial buildings are found which are modifications between residential and commercial. Meanwhile a new communal space appeared to replace the communal space that had been lost.